Lizards, Lineage and Latitude: Behavioural Responses to Microclimate Vary Latitudinally and Show Limited Acclimatisation to a Common Environment After Two Years - Deanne M. Trewartha; Stephanie S. Godfrey; Michael G. Gardner (Biology)
Climate change has negatively impacted species worldwide. Ectotherms, including reptiles, are at particular risk of local extirpation. Numerous reptile species vary in their climate response across latitude and altitude; therefore, understanding how climate change impacts populations is vital. Thermoregulation trades off with hydroregulation; therefore, both must be included when investigating response to microclimate. Here we investigated behavioural responses to temperature and relative humidity in three latitudinally distinct lineages of Tiliqua adelaidensis, a cryptic, burrow-dwelling endangered lizard endemic to South Australia. A monthly field-based approach distance method was adopted in the spring of 2022 in the wild and at a southerly trial translocation site. The behaviour of wild northern latitude lizards was linked with the microclimate, prioritising surface activity under moderate conditions. Wild and translocated northern lizards reduced approach distance and were only observed on the surface when base-of-burrow humidity was high, suggesting a plasticity lag or limit for this population. There was some evidence of translocation acclimatisation; however, our results suggest acclimatisation may take longer than two years and may vary with latitude of origin. While lineages may be limited in their ability to adjust to increasing temperatures under climate change, these lizards may cope with translocation as a mitigation strategy in the longer term.